PENGARUH KINERJA AUDITOR DAN TINGKAT PELATIHAN AUDITOR TERHADAP KUALITAS HASIL PEMERIKSAAN - Sudjono Sudjono (Universitas Bunda Mulia, 2017)
In response to implement and to keep transparancy dan accountability in public financial sector or private sector, audit have a major and absolute role. This role is to accomplish the expectation and the requirement from stakeholder. Therefore, writer feel necessary to have a research about audit quality and because of that writer have a picture that can be reliable. In this research, writer use three variables which is auditor performance, auditor training level, and audit result quality. The purpose of this research provides empirical evidence that audit result quality influenced by auditor performance and auditor training level. For this research method, writer use a double linier regression analysis test. In collecting primary data, writer use auditor from Auditama Keuangan Negara I BPK RI for 32 persons as respondens. There are a lot of research about audit quality, however there is a variable difference between this research and others. Other research use ability, knowledge, independency dan ethic associated with audit quality. This research use rewards expectation, duty perception for auditor performance variable and conceptual skill, technical training and moral education for auditor training level variable. The results of this research find that auditor performance variable and auditor training level variable influence audit result quality variable. As parsial and together, auditor performance variable and auditor training level variable have a positive correlation with audit result quality variable. However, there is limitation when writer set this study, for example audit application do not include as variable in this research. Other limitation is only 32 respondens that become sample for this research. This sample are not enough to represent auditor profession and to generalize the result of this research for auditor profession. In the future, writer suggest that on the similar research, a writer have to add more responden dan use other variable. So that research become more practical, relevan, useable for public and auditor profession. Keywords: transparancy; accountability; auditor performance; auditor training level, audit result quality; double linier regression analysis; auditor profession.